Research trends and hotspots in farmer and herdsman income: a visualization analysis using CiteSpace - Bai, Meiting; Wan, Ting; Chen, Qianhua; Yue, Beifan; Feng, Yanli; Ding, Wenqiang; Duan, Tingyu (Frontiers in Sustainable Food Systems, 2025)
The income of farmers and herdsmen is directly related to the prosperity and harmony of the entire society. Improving the income of farmers and herdsmen not only affects the living standards of individuals and families but also impacts the sustainability of society and the economic development of the country. To gain a global understanding of the research hotspots associated with the income of farmers and herdsmen, the study used the CiteSpace software to analyze the research publications and references on the income of farmers and herdsmen published between 1994 and 2023 and available in the Web of Science. The data collected included countries, institutions, journals, authors, keywords, co-citations, research focus and frontiers. The data showed a total of 14,726 literature, with the number of publications increasing significantly in 2013, and continuously from 2015 to 2022. The research hotspots focused on management and agriculture policy, land use and food systems, rural development, conservation and biodiversity. Most of the researches was involved the countries or district of developing countries in Africa and Asia. While the research levels include agricultural technology, climate change, sustainable development and policy at different scales. However, the research frontiers and trends focused on sustainable development, climate change, food security, agricultural techniques and policies. The present study provides knowledge and comments for further research on the global income of farmers and herdsmen.